ORTHOPTERA DIVERSITY AND ITS SEASONAL FLUCTUATIONS IN AGRICULTURAL AND FOREST ECOSYSTEMS OF WARANGAL DISTRICT, TELANGANA STATE, INDIA (CAHIERS MAGELLANES-NS, 2024)
Understanding the influence of habitat type on species diversity and abundance is crucial for effective ecosystem management. The objective of this study is to investigate the diversity of Orthoptera and analyze its seasonal fluctuations across agricultural and forest ecosystems in Warangal District, Telangana State, India. The study was conducted in Rajanpalle village, Gudur Mandal, Warangal District, Telangana State, India, a location within the Gudur forest zone and Pakhal Wildlife Sanctuary, offering a representative setting for comparing agricultural and forest ecosystems. Soil arthropods were sampled monthly from February 2015 to January 2017 across three seasons, using a transect method in both agricultural and forested areas, with the collected specimens preserved for analysis. Biodiversity was assessed using Shannon’s diversity index, along with other indices, to measure species richness and evenness in the studied ecosystems. The analysis reveals that the forest ecosystem consistently supports higher and more stable species diversity and evenness, as evidenced by a consistently high Shannon-Weiner Index across all seasons. In contrast, the agricultural ecosystem shows notable seasonal fluctuations in species abundance, with a significant decrease in diversity and evenness during the summer months. This variation is reflected in a lower Shannon-Weiner Index for agriculture, indicating less stable biodiversity. The findings highlight the forest’s capacity to maintain a balanced and resilient ecosystem year-round, while agricultural environments experience greater seasonal variability and reduced biodiversity.